Glass powder, conductive silver paste and preparation method thereof, front electrode and silicon solar cell

By using a glass powder combination composed of TeO2-MgO-Li2O and SiO2-Bi2O3-CuO-Li2O, a conductive silver paste suitable for the front electrode of silicon solar cells was prepared, which solved the problem that conductive silver paste in the prior art was difficult to take into account a variety of silicon solar cell technologies, and achieved the effect of high gate line peeling intensity and excellent photoelectric conversion efficiency.

CN114550969BActive Publication Date: 2025-04-25SHANGHAI SILVER PASTE SCI & TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210076615.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-21
Publication Date
2025-04-25
Estimated Expiration
2042-01-21

AI Technical Summary

Technical Problem

It is difficult for existing conductive silver paste to take into account a variety of silicon solar cell technologies, especially in terms of gate stripping intensity and photoelectric conversion efficiency.

Method used

A conductive silver paste suitable for the front electrode of silicon solar cells was prepared using a glass powder combination composed of TeO2-MgO-Li2O and SiO2-Bi2O3-CuO-Li2O, combined with spherical silver powder and an organic carrier.

Benefits of technology

This conductive silver paste has excellent gate stripping strength and excellent photoelectric conversion efficiency in a variety of silicon solar cell technologies, and is simple in process and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a conductive silver paste for a front electrode of a silicon solar cell and a glass powder thereof, wherein the glass powder comprises a first-state glass powder and a second-state glass powder, wherein the first-state glass powder mainly comprises at least one of W or Mo element oxides, TeO2, MgO and Li2O, and the second-state glass powder mainly comprises SiO2, Bi2O3, CuO and Li2O. The present invention also provides a preparation method of the conductive silver paste for a front electrode of a silicon solar cell, and a front electrode and a silicon solar cell comprising the conductive silver paste. The conductive silver paste can be widely applied to different types of silicon solar cell sheets, has high peel strength when combined with the battery, has a long service life, has low contact resistance, and has high photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of silicon solar cells, and in particular to glass powder for a front electrode of a silicon solar cell, conductive silver paste for a front electrode of a silicon solar cell and a preparation method thereof, a front electrode and a silicon solar cell. Background Art

[0002] Solving the energy problem of human development is still one of the most important topics at present. Nuclear energy and solar energy are the two main fossil energy alternatives that have gradually developed in this context. However, the use of nuclear energy may bring safety risks. To this day, humans are still unable to solve the environmental pollution caused by nuclear leakage. This will lead to the limitation of human use of nuclear energy in the next few decades or even hundreds of years, and it cannot replace fossil energy on a large scale as a clean energy or new energy. Therefore, solar energy is still the most effective new energy that can be widely used, clean and pollution-free, to replace fossil energy.

[0003] Solar cells are the most effective way to convert solar energy into energy and electricity that is easy to use and store. They have been widely studied, including silicon solar cells, perovskite structure solar cells, thin-film solar cells, heterojunction solar cells, etc. Among them, silicon solar cells are the most widely used and the most mature technology. Silicon solar cells are devices that use the photovoltaic effect of pn junctions to convert photons of sunlight to generate electricity. They are mainly composed of front electrodes, anti-reflection films, PN junctions, silicon substrates, back electrodes, etc. The front electrode is formed by screen printing, drying and sintering of conductive silver paste.

[0004] At present, with the development of technology, silicon solar cell technology has also become diversified, such as conventional polycrystalline, polycrystalline black silicon, polycrystalline diamond wire, conventional single crystal battery, perc single crystal, Se-perc single crystal, N-type battery, etc. There are many types of batteries, and the structure of anti-reflection film involving silicon nitride, titanium oxide, aluminum oxide, silicon oxide and other materials is complex and diverse, which makes it difficult for the conductive silver paste on the current market to take into account a variety of silicon solar cell technologies. The conductive silver paste of the silicon solar cell provided by the present invention can be widely adapted to batteries of various process and technical structures, and has excellent grid line peeling strength and excellent photoelectric conversion efficiency. Summary of the invention

[0005] The purpose of the present invention is to provide a glass powder of conductive silver paste for the front electrode of a silicon solar cell and a conductive silver paste containing the glass powder, which can be widely used in silicon solar cells of various processes and technical structures, and has excellent grid line peeling strength and excellent photoelectric conversion efficiency.

[0006] Another object of the present invention is to provide a method for preparing a conductive silver paste, which has fewer steps and is simple and practical.

[0007] Another object of the present invention is to provide a front electrode and a silicon solar cell comprising the above-mentioned glass powder or conductive silver paste, which can be widely applicable to silicon solar cells with various processes and technical structures. These silicon solar cells with different processes and technical structures all have better grid line peeling strength and better photoelectric conversion efficiency.

[0008] In order to achieve the above-mentioned object, the present invention provides a glass powder combination suitable for a conductive silver paste for a front electrode of a silicon solar cell, the glass powder combination comprising a first-state glass powder and a second-state glass powder, the first-state glass powder mainly comprising at least one of W or Mo element oxides, TeO2, MgO and Li2O, the second-state glass powder mainly comprising SiO2, Bi2O3, CuO and Li2O.

[0009] Furthermore, the first-state glass powder also includes modified oxides, and the modified oxides are oxides formed by the first series of elements of Bi, Pb, Na, K, Al, Zn, Cu, Ca, Si, Ge, Tl, B, Ce, Ti, Fe, Sb, V, Sn, Pr, Sr and Ba, or one or more substances that can be decomposed to obtain oxides formed by the first series of elements.

[0010] Furthermore, taking the total molar number of each oxide contained in the first-state glass powder as 100%, the molar percentage of each oxide in the first-state glass powder is as follows:

[0011]

[0012]

[0013] Furthermore, the second-state glass powder also includes additives, which are one or more of oxides formed by the second series of elements of Pb, Zn, W, Ge, B, Sb, Te and Fe, or substances that can be decomposed to obtain oxides formed by the second series of elements.

[0014] Furthermore, taking the total molar number of each oxide contained in the second-state glass powder as 100%, the molar percentage of each oxide in the second-state glass powder is as follows:

[0015]

[0016] Furthermore, the particle size of the glass powder is 0.2-10.0 μm, the softening point of the first-state glass powder is 50° C.-150° C. lower than the softening point of the second-state glass powder, and the mixing mass ratio of the first-state glass powder and the second-state glass powder is not less than 1:3.

[0017] The present invention also provides a conductive silver paste for a front electrode of a silicon solar cell. Taking the total weight of the conductive silver paste as 100%, the conductive silver paste comprises:

[0018]

[0019] Furthermore, the silver powder is spherical silver powder, the particle size of the silver powder is 0.5-4.0 μm, and D50 is 1.0-2.0 μm.

[0020] Furthermore, the organic carrier comprises an organic solvent, an organic resin, a thickener, a defoamer and a curing agent. Based on the total weight of the organic carrier being 100%, the content of each component is as follows:

[0021]

[0022]

[0023] The present invention also provides a method for preparing a conductive silver paste for a front electrode of a silicon solar cell, the method comprising the steps of: preparing a first-state glass powder and a second-state glass powder, the first-state glass powder comprising at least one of W or Mo element oxides, TeO2, MgO and Li2O, the second-state glass powder comprising SiO2, Bi2O3, CuO and Li2O, the first-state glass powder or the second-state glass powder being obtained by weighing the constituent raw materials according to a mass ratio, mixing, melting, quenching, drying and crushing, the raw materials of the first-state glass powder and the second-state glass powder being oxides of corresponding elements or substances that can be decomposed by heating to obtain oxides of corresponding elements; preparing an organic carrier, the organic carrier comprising an organic solvent, an organic resin, a thickener, a defoaming agent and a curing agent, the organic carrier being obtained by mixing, water bath heating, centrifugal dispersion and cooling; and providing silver powder, mixing, stirring, rolling and filtering the silver powder, the first-state glass powder, the second-state glass powder and the organic carrier to obtain the conductive silver paste.

[0024] The present invention also provides a front electrode of a silicon solar cell, wherein the front electrode is obtained by printing the conductive silver paste of the front electrode of the silicon solar cell described above onto a crystalline silicon cell sheet by screen printing or spraying, and then drying and sintering.

[0025] The present invention also provides a silicon solar cell, which comprises the front electrode as described above.

[0026] Compared with the prior art, the first-state glass powder used in the present invention is a glass powder mainly composed of TeO2-MgO-Li2O. Compared with the traditional glass powder mainly composed of TeO2-PbO-Li2O, the lead content is greatly reduced, and it can even be completely lead-free, which reduces lead pollution. Therefore, TeO2-MgO-Li2O glass powder is more environmentally friendly than traditional glass powder; at the same time, TeO2-MgO-Li2O glass powder uses high-melting-point magnesium oxide to replace a large amount of low-melting-point lead oxide, bismuth oxide, zinc oxide and other substances to improve the viscosity and surface tension of the glass liquid, which well overcomes the problem that the traditional glass powder has too strong fluidity at the low temperature stage and is insufficient to assist the sintering of silver powder, and improves the sintering effect of the glass liquid on the silver powder. In addition, the Te The O2-MgO-Li2O glass powder uses a large amount of WO3 and MoO3 to replace the traditional SiO2. The tungsten and molybdenum elements can significantly reduce the high-temperature viscosity and surface tension of the glass liquid in the high-temperature stage, which well solves the problem that the viscosity of the glass liquid in the high-temperature stage is also high due to the high magnesium content, so that the glass liquid can flow and corrode the insulating layer on the surface of the battery well in the high-temperature stage to form an excellent ohmic contact; thereby creating the excellent performance of the TeO2-MgO-Li2O glass powder of the present invention, the low-temperature glass liquid has high viscosity and high surface tension, and the high-temperature glass liquid has low viscosity and low surface tension, so that the sintering effect on the silver powder is good, the grid line peeling strength is high, the corrosion effect on the glass interface is good, the contact effect is good, and the electrical performance is excellent.

[0027] The present invention uses a first-state glass powder mainly composed of TeO2-MgO-Li2O, and a second-state glass powder mainly composed of SiO2-Bi2O3-CuO-Li2O, to further enhance the sintering-aiding effect of the silver powder and the contact effect with the silver paste. The second-state glass powder is also a low-lead or lead-free glass powder. The second-state glass powder has a high silicon content and contains relatively high bismuth oxide and copper oxide, which results in a relatively high softening point of the glass. When the mass ratio of the first-state glass powder to the second-state glass powder is not less than 1:3, the two can be well mutually melted. The softening point of the second-state glass powder is 50°C to 150°C higher than that of the first-state glass powder, which well compensates for the problem of low viscosity of the first-state glass powder in the high-temperature zone, and ensures that the glass liquid can also well assist the sintering of the silver layer in the high-temperature stage. At the same time, near the highest sintering temperature zone, the first-state glass liquid and the second-state glass liquid gradually merge with each other, which results in a large amount of silicon elements in the second-state glass liquid entering the first-state glass liquid. It reduces the destructiveness of the first-state glass liquid to the PN junction layer, increases the opening voltage of the battery cell, and promotes the large-scale precipitation of the silver element melted in the first-state glass liquid, forming a better contact effect at the contact interface, lower contact resistance, and improving the electrical performance of the battery.

[0028] Due to the different surface structures of different types of battery cells, the adhesion effect and corrosion effect of the conductive silver paste after sintering on their surfaces are very different, and it is difficult to use a conductive silver paste on a variety of different battery cells. The conductive silver paste provided by the present invention comprises a first-state glass powder and a second-state glass powder, has an excellent sintering effect, and the grid line peeling strength is greatly improved, which meets the peeling strength requirements for use on various battery cells. The characteristics of the first-state glass powder and the second-state glass powder are combined with each other to achieve excellent contact effects and excellent electrical properties for battery cells with different characteristics.

[0029] The conductive silver paste provided by the present invention is compatible with battery cells produced by various processes. The process for producing the conductive silver paste is simple and the cost is low. The silicon solar cells and the front electrodes thereof prepared by the conductive silver paste include various types of battery front electrodes and batteries such as conventional polycrystalline, polycrystalline black silicon, polycrystalline diamond wire, conventional single crystal cells, perc single crystal, and Se-perc single crystal, and have wide practicality. DETAILED DESCRIPTION

[0030] The "range" disclosed herein is in the form of a lower limit and an upper limit. It can be one or more lower limits, and one or more upper limits, respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e., any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a specific parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, if there is no special explanation, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0031] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution. In the present invention, unless otherwise specified, all steps mentioned herein can be performed sequentially or randomly, but preferably sequentially.

[0032] The present embodiment provides a silicon solar cell, which is mainly composed of a front electrode, an anti-reflection film, a PN junction, a silicon substrate, a back electrode, etc. The front electrode is made by printing a conductive silver paste on a crystalline silicon cell by screen printing or spraying, and then drying and sintering. The present embodiment provides a conductive silver paste, which, based on the total weight of the conductive silver paste as 100%, comprises 79.00% to 93.00% silver powder, 0.30% to 8.00% first-state glass powder, 0.10% to 3.00% second-state glass powder, and 5.00% to 20.00% organic carrier. Among them, the silver powder is spherical silver powder, the particle size of the silver powder is 0.5 to 4.0 μm, and D50 is 1.0 to 2.0 μm. Based on the total weight of the organic vehicle being 100%, the organic vehicle comprises 20.0% to 80.0% of an organic solvent, 2.0% to 20% of an organic resin, 1.0% to 20.0% of a thickener, 0.1% to 5.0% of a defoaming agent, and 0.1% to 5.0% of a curing agent.

[0033] The glass powder suitable for the above-mentioned conductive silver paste provided in this embodiment includes a first-state glass powder and a second-state glass powder, and the first-state glass powder includes at least one of W or Mo element oxides, TeO2, MgO and Li2O. The first-state glass powder also includes modified oxides, and the modified oxides are one or more of the oxides formed by the first series of elements of Bi, Pb, Na, K, Al, Zn, Cu, Ca, Si, Ge, Tl, B, Ce, Ti, Fe, Sb, V, Sn, Pr, Sr and Ba or substances that can be decomposed to obtain oxides formed by the first series of elements. Taking the total molar number of each oxide contained in the first-state glass powder as 100%, the molar percentages of each oxide in the first-state glass powder are as follows: TeO2 is 20.0% to 50.0%, MgO is 5.0% to 25.0%, Li2O is 10.0% to 30.0%, W or Mo element oxides are 2.0% to 15.0%, and modified oxides are 0.1% to 30.0%.

[0034] The second state glass powder includes SiO2, Bi2O3, CuO and Li2O. The second state glass powder also includes additives, and the additives are one or more of the oxides formed by the second series elements of Pb, Zn, W, Ge, B, Sb, Te and Fe or substances that can be decomposed to obtain the oxides formed by the second series elements. Taking the total molar number of each oxide contained in the second state glass powder as 100%, the molar percentage of each oxide in the second state glass powder is as follows: SiO2 is 15.0% to 60.0%, Bi2O3 is 1.0% to 10.0%, CuO is 2.0% to 15.0%, Li2O is 15.0% to 40.0%, and the additive is 0.1% to 25.0%.

[0035] The particle size of the glass powder is 0.2-10.0 μm, the softening point of the first-state glass powder is 50° C.-150° C. lower than the softening point of the second-state glass powder, and the mixing mass ratio of the first-state glass powder to the second-state glass powder is not less than 1:3.

[0036] Preparation of conductive silver paste:

[0037] The first-state glass powder and the second-state glass powder are prepared by calculating, weighing, mixing, melting, quenching, drying and crushing according to the designed formulas of the first-state glass powder and the second-state glass powder to prepare the first-state glass powder and the second-state glass powder with suitable particle sizes; the raw materials of the first-state glass powder and the second-state glass powder are oxides of corresponding elements or substances that can be decomposed by heating to obtain oxides of corresponding elements;

[0038] preparing an organic carrier by calculating, weighing, mixing, heating in a water bath, centrifugally dispersing, and cooling according to a designed organic carrier formula to prepare the organic carrier;

[0039] Silver powder is provided, and the silver powder, first-state glass powder, second-state glass powder and organic carrier are calculated, weighed, mixed, stirred, rolled and filtered according to a set mass ratio to obtain a conductive silver paste.

[0040] The conductive silver paste is printed onto the crystalline silicon cell by screen printing or spraying, and then dried and sintered to obtain a front electrode containing the conductive silver paste.

[0041] The following is described in conjunction with specific embodiments 1-10:

[0042] Preparation of first-state glass powder: The first-state glass powder raw material oxide or the compound or composite that can be decomposed into the inorganic oxide is calculated, weighed, mixed, melted, quenched, crushed, and graded in sequence to make the corrosion-resistant glass powder B1-B6. The specific composition ratio of each glass powder is shown in Table 1.

[0043] Preparation of second-state glass powder: The second-state glass powder raw material oxide or the compound or composite that can be decomposed into the inorganic oxide is calculated, weighed, mixed, melted, quenched, crushed, and graded in sequence to make the corrosion-resistant glass powder C1-C4. The specific composition ratio of each glass powder is shown in Table 2.

[0044] Preparation of organic carrier: The organic solvent, organic resin, thickener, defoamer, and curing agent raw materials for making the organic carrier are calculated according to mass percentage, weighed, mixed, stirred, heated in a water bath, dispersed uniformly, and then cooled to obtain the organic carrier P1. The organic solvent, organic resin, thickener, defoamer, and curing agent suitable for organic carriers in the prior art are also suitable for the present invention, and will not be described in detail here.

[0045] Preparation of conductive silver paste: Two kinds of glass powders commonly used in the market were selected and numbered A1 and A2. A1 glass powder was E066 positive silver glass powder produced by Korea Best Company, and A2 glass powder was A105 positive silver glass powder produced by Korea Phoenix Company, for use as comparative examples. The prepared silver powder, glass powder, and organic carrier were calculated according to the mass percentage composition of the conductive silver paste, weighed, and then stirred evenly using a mixer, and finally rolled using a three-roller mill, and filtered to obtain the conductive silver pastes D1-D10, as shown in Table 3.

[0046] The prepared conductive silver paste is screen-printed onto the surface of the battery cells produced by different processes, and then dried, sintered and cooled to obtain a silicon solar cell containing printed silver grid line electrodes. The obtained silicon solar cell is subjected to efficiency test and grid line peeling strength test. The test results are shown in Table 4.

[0047] Table 1 Molar composition of first-state glass powder embodiment (mol%)

[0048]

[0049]

[0050] Table 2 Molar composition of the second state glass powder embodiment (mol%)

[0051] name C1 C2 C3 C4 <![CDATA[SiO2]]> 59.9 15.2 45.0 36.4 <![CDATA[Bi2O3]]> 4.1 9.6 5.8 6.0 CuO 6.4 14.7 8.5 2.1 <![CDATA[Li2CO3]]> 15.5 39.5 22.7 30.7 PbO 3.8 3.2 2.1 ZnO 8.0 1.5 14.1 <![CDATA[WO3]]> 9.2 1.8 5.4 <![CDATA[GeO2]]> 3.3 3.0 0.7 <![CDATA[B2O3]]> 2.0 1.0 0.5 <![CDATA[TiO2]]> 1.0 <![CDATA[TeO2]]> 1.3 1.0 MgO 2.5 7.5 2.0 <![CDATA[Na2CO3]]> 1.5 0.5 <![CDATA[Sb2O3]]> 1.0

[0052] Table 3 Example silver paste composition table (%)

[0053]

[0054]

[0055] It can be seen from Table 4 that the silicon solar cells prepared with the conductive silver paste provided in the embodiment of the present invention, D3~D10 conductive silver pastes have higher photoelectric conversion efficiency in polycrystalline cells, conventional single crystal cells, Perc-single crystal and Se-Perc-single crystal than the comparative examples D1 and D2, and the grid line peeling strength on different cells is obviously superior, and the peeling tensile force is much higher than the comparative example. On polycrystalline and conventional single crystal cells, D1 and D2 have little difference from the silver paste of the embodiment of the present invention, but on Perc-single crystal and Se-Perc-single crystal, the difference is obvious. D1 and D2 have EL problems to varying degrees, and the efficiency is obviously biased. It can be seen that the conductive silver paste provided by the present invention is compatible with cells of various processes, can be widely used in polycrystalline cells, conventional single crystal cells, Perc single crystal, Se-perc single crystal, has high grid line peeling strength and high photoelectric conversion efficiency.

[0056] Compared with the prior art, the first-state glass powder used in the present invention is a glass powder mainly composed of TeO2-MgO-Li2O. Compared with the traditional glass powder mainly composed of TeO2-PbO-Li2O, the lead content is greatly reduced, and it can even be completely lead-free, which reduces lead pollution. Therefore, TeO2-MgO-Li2O glass powder is more environmentally friendly than traditional glass powder; at the same time, TeO2-MgO-Li2O glass powder uses high-melting-point magnesium oxide to replace a large amount of low-melting-point lead oxide, bismuth oxide, zinc oxide and other substances to improve the viscosity and surface tension of the glass liquid, which well overcomes the problem that the traditional glass powder has too strong fluidity at the low temperature stage and is insufficient to assist the sintering of silver powder, and improves the sintering effect of the glass liquid on the silver powder. In addition, the Te The O2-MgO-Li2O glass powder uses a large amount of WO3 and MoO3 to replace the traditional SiO2. The tungsten and molybdenum elements can significantly reduce the high-temperature viscosity and surface tension of the glass liquid in the high-temperature stage, which well solves the problem that the viscosity of the glass liquid in the high-temperature stage is also high due to the high magnesium content, so that the glass liquid can flow and corrode the insulating layer on the surface of the battery well in the high-temperature stage to form an excellent ohmic contact; thereby creating the excellent performance of the TeO2-MgO-Li2O glass powder of the present invention, the low-temperature glass liquid has high viscosity and high surface tension, and the high-temperature glass liquid has low viscosity and low surface tension, so that the sintering effect on the silver powder is good, the grid line peeling strength is high, the corrosion effect on the glass interface is good, the contact effect is good, and the electrical performance is excellent.

[0057] The present invention uses a first-state glass powder mainly composed of TeO2-MgO-Li2O, and a second-state glass powder mainly composed of SiO2-Bi2O3-CuO-Li2O, to further enhance the sintering-aiding effect of the silver powder and the contact effect with the silver paste. The second-state glass powder is also a low-lead or lead-free glass powder. The second-state glass powder has a high silicon content and contains relatively high bismuth oxide and copper oxide, which results in a relatively high softening point of the glass. When the mass ratio of the first-state glass powder to the second-state glass powder is not less than 1:3, the two can be well mutually melted. The softening point of the second-state glass powder is 50°C to 150°C higher than that of the first-state glass powder, which well compensates for the problem of low viscosity of the first-state glass powder in the high-temperature zone, and ensures that the glass liquid can also well assist the sintering of the silver layer in the high-temperature stage. At the same time, near the highest sintering temperature zone, the first-state glass liquid and the second-state glass liquid gradually merge with each other, which results in a large amount of silicon elements in the second-state glass liquid entering the first-state glass liquid. It reduces the destructiveness of the first-state glass liquid to the PN junction layer, increases the opening voltage of the battery cell, and promotes the large-scale precipitation of the silver element melted in the first-state glass liquid, forming a better contact effect at the contact interface, lower contact resistance, and improving the electrical performance of the battery.

[0058] Due to the different surface structures of different types of battery cells, the adhesion effect and corrosion effect of the conductive silver paste after sintering on their surfaces are very different, and it is difficult to use a conductive silver paste on a variety of different battery cells. The conductive silver paste provided by the present invention comprises a first-state glass powder and a second-state glass powder, has an excellent sintering effect, and the grid line peeling strength is greatly improved, which meets the peeling strength requirements for use on various battery cells. The characteristics of the first-state glass powder and the second-state glass powder are combined with each other to achieve excellent contact effects and excellent electrical properties for battery cells with different characteristics.

[0059] The conductive silver paste provided by the present invention is compatible with battery cells produced by various processes. The process for producing the conductive silver paste is simple and the cost is low. The silicon solar cells and the front electrodes thereof prepared by the conductive silver paste include various types of battery front electrodes and batteries such as conventional polycrystalline, polycrystalline black silicon, polycrystalline diamond wire, conventional single crystal cells, perc single crystal, and Se-perc single crystal, and have wide practicality.

[0060] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention are still within the scope covered by the present invention.

Claims

1. A glass powder suitable for conductive silver paste of the front electrode of a silicon solar cell, characterized in that: The glass powder includes a first-state glass powder and a second-state glass powder, wherein the first-state glass powder mainly includes at least one of W or Mo element oxides, TeO2, MgO and Li2O, and the second-state glass powder mainly includes SiO2, Bi2O3, CuO and Li2O; Taking the total molar number of each oxide contained in the second-state glass powder as 100%, the molar percentage of each oxide in the second-state glass powder is as follows: SiO2 15.0%~60.0%; Bi2O31.0%~10.0%; CuO2.0%~15.0%; Li2O15.0%~40.0%; Additives 0.1%~25.0%; Taking the total molar number of each oxide contained in the first-state glass powder as 100%, the molar percentage of each oxide in the first-state glass powder is as follows: TeO2 20.0%~50.0%; MgO5.0%~25.0%; Li2O10.0%~30.0%; W or Mo element oxide 2.0%~15.0%; Modified oxide 0.1%~30.0%.

2. The glass powder according to claim 1, characterized in that: The first-state glass powder also includes modified oxides, which are oxides formed by the first series of elements of Bi, Pb, Na, K, Al, Zn, Cu, Ca, Si, Ge, Tl, B, Ce, Ti, Fe, Sb, V, Sn, Pr, Sr and Ba, or one or more substances that can be decomposed to obtain oxides formed by the first series of elements.

3. The glass powder according to claim 1, characterized in that The second-state glass powder also includes additives, which are one or more oxides formed by the second series of elements of Pb, Zn, W, Ge, B, Sb, Te and Fe, or substances that can be decomposed to obtain oxides formed by the second series of elements.

4. The glass powder according to claim 1, characterized in that: The particle size of the glass powder is 0.2-10.0 μm, the softening point of the first-state glass powder is 50° C.-150° C. lower than the softening point of the second-state glass powder, and the mixing mass ratio of the first-state glass powder to the second-state glass powder is not less than 1:

3.

5. A conductive silver paste suitable for the front electrode of a silicon solar cell, characterized in that: Taking the total weight of the conductive silver paste as 100%, the conductive silver paste comprises: Silver powder 79.00%~93.00%; 0.50% to 6.00% of the first-state glass powder according to any one of claims 1 to 4; 0.10% to 3.00% of the second state glass powder according to any one of claims 1 to 4; Organic carrier 5.00%~17.00%.

6. The conductive silver paste according to claim 5, characterized in that: The silver powder is spherical silver powder, the particle size of the silver powder is 0.5-4.0 μm, and D50 is 1.0-2.0 μm.

7. The conductive silver paste according to claim 5, characterized in that: The organic carrier comprises an organic solvent, an organic resin, a thickener, a defoamer and a curing agent. Based on the total weight of the organic carrier being 100%, the content of each component is as follows: Organic solvent 40.0%~80.0%; Organic resin 2.0%~30%; Thickener 1.0%~30.0%; Defoaming agent 0.1%~5.0%; Curing agent 0.1%~5.0%.

8. A method for preparing a conductive silver paste for a front electrode of a silicon solar cell, characterized in that: The preparation method comprises the steps of: Prepare a first-state glass powder and a second-state glass powder, wherein the first-state glass powder includes at least one of W or Mo element oxides, TeO2, MgO and Li2O, and the second-state glass powder includes SiO2, Bi2O3, CuO and Li2O, and the first-state glass powder or the second-state glass powder is obtained by mixing, melting, quenching, drying and pulverizing, and the raw materials of the first-state glass powder and the second-state glass powder are oxides of corresponding elements or substances that can be decomposed by heating to obtain oxides of corresponding elements; preparing an organic carrier, wherein the organic carrier comprises an organic solvent, an organic resin, a thickener, a defoamer and a curing agent, and the organic carrier is prepared by mixing, heating in a water bath, centrifugally dispersing and cooling; as well as Providing silver powder, and preparing the conductive silver paste by mixing, stirring, rolling and filtering the silver powder, first-state glass powder, second-state glass powder and an organic carrier; Taking the total molar number of each oxide contained in the second-state glass powder as 100%, the molar percentage of each oxide in the second-state glass powder is as follows: SiO2 15.0%~60.0%; Bi2O31.0%~10.0%; CuO2.0%~15.0%; Li2O15.0%~40.0%; Additives 0.1%~25.0%; Taking the total molar number of each oxide contained in the first-state glass powder as 100%, the molar percentage of each oxide in the first-state glass powder is as follows: TeO2 20.0%~50.0%; MgO5.0%~25.0%; Li2O10.0%~30.0%; W or Mo element oxide 2.0%~15.0%; Modified oxide 0.1%~30.0%.

9. A front electrode of a silicon solar cell, characterized in that: The front electrode is prepared by printing the conductive silver paste of the front electrode of the silicon solar cell according to any one of claims 5 to 7 onto the crystalline silicon cell by screen printing or spraying, and then drying and sintering.

10. A silicon solar cell, characterized in that: The silicon solar cell comprises the front electrode as claimed in claim 9.

Citation Information

Patent Citations

  • KR20190113131A